2017
DOI: 10.3390/jmse5010008
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Development of an Operational Forecast System for the Florida Coast

Abstract: A nowcasting and forecasting system for storm surge, inundation, waves, and baroclinic flow for the Florida coast has been developed. The system is based on dynamically coupled CH3D and SWAN models and can use a variety of modules to provide different input forcing, boundary and initial conditions. The system is completely automated and operates unattended at pre-scheduled intervals as well as in event-triggered mode in response to Atlantic-basin tropical cyclone advisories issued by the National Hurricane Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Paramygin et al. (2017) applied the CH3D model nested in a large‐scale ADCIRC (Luettich et al., 1992) grid and identified that enhanced resolution in coastal zones is possible using this approach; however, the large‐scale grid simulations require significant computational time. Recently, Dietrich et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paramygin et al. (2017) applied the CH3D model nested in a large‐scale ADCIRC (Luettich et al., 1992) grid and identified that enhanced resolution in coastal zones is possible using this approach; however, the large‐scale grid simulations require significant computational time. Recently, Dietrich et al.…”
Section: Introductionmentioning
confidence: 99%
“…An early study by Robinson et al (1996) applied the Harvard ocean prediction system in a forecast configuration and highlighted the importance of effective data assimilation for accurate model results. Paramygin et al (2017) applied the CH3D model nested in a large-scale ADCIRC (Luettich et al, 1992) grid and identified that enhanced resolution in coastal zones is possible using this approach; however, the large-scale grid simulations require significant computational time. Recently, Dietrich et al (2018) found that atmospheric forecasts produce more accurate coastal forecasts compared to parametric hurricane wind models.…”
mentioning
confidence: 99%
“…Inevitably the foundations of operational global forecasts are being leveraged for localised downscaled dynamic operational ocean models: e.g., [15][16][17][18].…”
Section: Routine Sea Level and Operationsmentioning
confidence: 99%